Analisis Penerapan Pendekatan Pembelajaran Berdiferensiasi pada Mata Pelajaran Informatika di SMP Negeri 33 Padang - Wahyuni, Putri; Yeni J, Fetri; Zen, Zelhendri; Anugrah, Septriyan (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the implementation of a differentiated approach in the subject of Computer Science. This study focuses on how teachers plan, implement, and evaluate differentiated instruction, as well as identifying the challenges faced in the prosess. This researxh uses a descriptive qualitative approach. Data were collected through interviews, classroom observations, and documentation. The research subjects incude an Informatics teacher and eighth-grades students. Data analysis was conducted through data reduction, data display, and conclusion drawing. Data validity was ensured through source and method source triangulation. The teacher planned differentiated instruction by considering students’ characteristics, although the planning was still general. During implementation, the teacher applied student grouping and offered varied tasks. Evaluation was conducted through PH results, showing that moast students achieved score in the “fairly good” category. The planning and implementation of differentiated instruction were not yet optimal due to several challenges. Internal factors such as low student discipline, inappropriate behavior, and lack of motivation hindered effective learning. External factors, including inadequate school facilities sych as damaged computers and unstable internet connections, also disrupted the learning process.